2018
DOI: 10.18203/2349-2902.isj20181604
|View full text |Cite
|
Sign up to set email alerts
|

A study on clinical profile and management of mastalgia

Abstract: INTRODUCTIONMastalgia, or breast pain, is a common complaint that may affect up to 70% of women in their lifetime.1 It is not unusual for women to have 2-3 days of mild breast pain premenstrually but 8-30% of women report moderate to severe breast pain with duration of 5 or more days each month.2 Fifteen percent of women who present to a breast clinic with mastalgia will require treatment. 3Breast pain is classified as cyclical mastalgia, noncyclical mastalgia and non-specific extra-mammary pain. Cyclical mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…Clinical presentations in initial visit showed maximum respondent had cyclical mastalgia (57.78%) and 42.22% had non-cyclical mastalgia. Similar observation was noted in a previous study by Rajswaroob et al 17 and Nirhale et al 8 In this study maximum respondents (60%) had both breasts involvement, 26.7% had left breast and 13.3% had right breast involvement. In a previous study by Sangma MB et al 18 observed maximum respondents had right breast involvement (48%), the left breast was affected in 40% patients while only 12% cases both breasts were affected, that differs from our observation.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Clinical presentations in initial visit showed maximum respondent had cyclical mastalgia (57.78%) and 42.22% had non-cyclical mastalgia. Similar observation was noted in a previous study by Rajswaroob et al 17 and Nirhale et al 8 In this study maximum respondents (60%) had both breasts involvement, 26.7% had left breast and 13.3% had right breast involvement. In a previous study by Sangma MB et al 18 observed maximum respondents had right breast involvement (48%), the left breast was affected in 40% patients while only 12% cases both breasts were affected, that differs from our observation.…”
Section: Discussionsupporting
confidence: 92%
“…Almost similar observation was seen in some previous study by Rajswaroob et al 17 and Neogi P et al 21 and Nirhale et al 8 There are some limitations of our study. This study was performed in a single tertiary care hospital among small available population size.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this case, a single patient occasionally complained of several adverse symptoms. In several earlier research by Rajswaroob et al [18] , Neogi et al [19] and Nirhale et al [20] , a nearly same observation is made. In our study, the reported side effects due to Primrose use were comparable to Mostary et al [21] who reported bloating in 6.7% and headache in 2.2% of patients treated with primrose.…”
Section: Discussionsupporting
confidence: 65%